2013
DOI: 10.1371/journal.pone.0056376
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Protease and Protease Inhibitors in a Mouse Model of Human Pelvic Organ Prolapse

Abstract: Mice deficient for the fibulin-5 gene (Fbln5−/−) develop pelvic organ prolapse (POP) due to compromised elastic fibers and upregulation of matrix metalloprotease (MMP)-9. Here, we used casein zymography, inhibitor profiling, affinity pull-down, and mass spectrometry to discover additional protease upregulated in the vaginal wall of Fbln5−/− mice, herein named V1 (25 kDa). V1 was a serine protease with trypsin-like activity similar to protease, serine (PRSS) 3, a major extrapancreatic trypsinogen, was optimum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Two studies have now demonstrated that the FBLN5 protein can be cleaved by serine proteases23 24 and increased levels of this cleaved form of FBLN5 protein were demonstrated in the skin of aged mice 23. This is intriguing as on the one hand COPD has been regarded as an aging lung disease25 26 and on the other hand increased serine protease activity is present in COPD lungs, which is thought to play an important role in emphysematous lung tissue destruction 27 28.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies have now demonstrated that the FBLN5 protein can be cleaved by serine proteases23 24 and increased levels of this cleaved form of FBLN5 protein were demonstrated in the skin of aged mice 23. This is intriguing as on the one hand COPD has been regarded as an aging lung disease25 26 and on the other hand increased serine protease activity is present in COPD lungs, which is thought to play an important role in emphysematous lung tissue destruction 27 28.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that a switch from phenotypic smooth muscle cells (SMCs) to myofibroblast differentiation could be the underlying cause of structural modifications in the tunica muscularis of the anterior vaginal wall. Indeed, SMCs undergo an aberrant switch from a contractile to a synthetic extracellular matrix, producing a phenotype consequent to their trans-differentiation into myofibroblasts (Smith et al 1990;Budatha et al 2013;Severi et al 2014;Vetuschi et al 2016). Therefore, the switch from type I to type III occurring in POP entails a greater distensibility, but at the same time fragility, of the wall itself (Tremollieres, 2010;Kannan et al 2011;Kerkhof et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in muscularis propria in POP also include a reduction in the concentration of elastic fibres and an imbalance in the extracellular matrix turnover, due to the overexpression of MMPs and a simultaneous reduction in their inhibitors (Budatha et al 2013;Shynlova et al 2013;Yucel et al 2013;De Landsheere et al 2014;Vetuschi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Usage of (iii) as an evidence was based on the rationale that heart valve, cartilage, tendon, and bone development share common regulatory pathways 26 . The genes ADAMTS1 12 , MYH3 27 and SERPINE1 28 were up-regulated in POP tissues. Polymorphic variants in the genes LIN28B 29 and AGT 30 were associated with POP and mitral valve prolapse (MVP) respectively.…”
Section: Resultsmentioning
confidence: 94%